Pengaruh Fee Audit, Audit Rotation, dan Audit Tenure terhadap Audit Quality - Sudarmadi Sudarmadi; Meilynda Safitri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effect of audit fees, audit rotation, and audit tenure on audit quality in insurance subsector companies listed on the Indonesia Stock Exchange during 2019–2024. The research applies a quantitative associative design using secondary data obtained from annual reports and audited financial statements. From a population of 18 companies, purposive sampling produced 10 companies observed for six years, resulting in 60 firm-year observations. Audit quality is measured using a binary proxy based on the use of Big Four and non-Big Four public accounting firms, while audit fees, audit rotation, and audit tenure are treated as explanatory variables. Data were processed with Microsoft Excel and analyzed through binary logistic regression using EViews 12. The likelihood ratio test shows a probability value of 0.000009, indicating that audit fees, audit rotation, and audit tenure jointly have a significant effect on audit quality. Partially, audit fees have a positive and significant effect, with a coefficient of 0.000206 and a probability value of 0.0003. Audit rotation has a negative but statistically insignificant effect, with a probability value of 0.5726, while audit tenure has a positive but statistically insignificant effect, with a probability value of 0.6174. These findings indicate that adequate audit remuneration is associated with a greater likelihood of higher audit quality, whereas auditor replacement and engagement length alone do not determine audit quality. The study emphasizes the importance of reasonable fee determination, effective audit committee oversight, and professional quality-control mechanisms.